WALI NIKAH DALAM KITAB FATH AL-QADÎR KARYA IBNU HIMMAM (Tinjauan Deskriptif Analitis Tematis) - Dwi Sagita Akbar (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2018)
Marriage has terms and harmony that have been established both in the Qur'an and in the Hadith. One of the conditions in a marriage contract is the presence of a parent (guardian) and a representative. Trusteeship, which was originally an ancient Arab culture that eventually became the Prophet's Sunnah was an absolute requirement for women to be able to do a marriage. What is meant by guardian in marriage is someone who acts on behalf of the bride in a marriage contract. Indeed there is no single verse of the Koran that clearly (explicitly) explains the existence of a guardian in a marriage contract. But there are only verses that can be understood to require the existence of a guardian as in the letter Al-Baqarah verse 221. This article briefly describes the guardian of marriage contained in the Fath Qadir Ibn Himmam. The book of Fath al-Qadir by Ibn Himmam was chosen to be the main source of study because it was one of the monumental works of all times in the field of Islamic Sciences especially for the study of Islamic law and was born from one of the famous Jurists to the present. The story of the Fath Qadir book is explained that according to Ibn Himmam guardianship in marriage is divided into two types, namely nadab / musthab and ijbar guardianship